MBRS-31. GERMLINE MICROSATELLITE SIGNATURE RELIABLY DIFFERENTIATES CHILDREN WITH MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Rivero-Hinojosa, Samuel; Kinney, Nicholas; Garner, Harold; Rood, Brian
Abstract: The genetic events leading to medulloblastoma initiation, and therefore the ability to determine who is at risk and why, are still unknown. Microsatellites are short tandem repeated sequences that comprise ~3% of the genome. The number of repeats varies between individuals and are often non-randomly associated with disease, including several cancers such as breast, glioma, lung and ovarian. We have developed a novel approach for identifying and validating a microsatellite signature set for medulloblastoma tumors using germline DNA. Analyzing germline DNA sequence from a training set of 120 medulloblastoma subjects and 425 healthy controls, we have identified a set of 139 microsatellite loci whose genotype are significantly different between medulloblastoma subjects and controls. Using an iterative classification algorithm, we found a subset of 43 microsatellites able to distinguish medulloblastoma subjects from controls with a sensitivity and specificity of 0.88 and 0.92, respectively. This signature set was validated in an independent dataset with greater sensitivity and specificity. Analysis of the minor alleles of those 139 informative loci demonstrates that these loci are more mutable in medulloblastoma patients than controls. Finally, a downstream analysis of the genes harboring these microsatellite loci revealed significantly enriched pathways (Autophagy and mTOR signaling) and genes associated with cell cycle and DNA replication, recombination, and repair. Interestedly, we identified two exonic microsatellites in the transcription factors RAI1 and BCL6B associated with medulloblastoma. This study demonstrates that medulloblastoma-specific microsatellite variations in the germline DNA can distinguish individuals with medulloblastoma as well as provide insight into mechanisms of predisposition.